2022
DOI: 10.1155/2022/4982047
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Different Types of Early Restrictive Fluid Resuscitation on Immune Function and Multiorgan Damage on Hemorrhagic Shock Rat Model in a Hypothermic Environment

Abstract: Objective. This study was aimed at investigating the effects of different types of fluid restriction fluid resuscitation on the immune dysfunction and organ injury of hemorrhagic shock rats under a hypothermic environment. Methods. SD rats were divided into sham operation group (SHAM), hemorrhagic shock model group (HS), crystal liquid limited resuscitation group (CRLLR), colloidal liquid limited resuscitation group (COLLR), and nonlimited resuscitation group (NLR); rats in each group were placed in a low-temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…According to Hongmin Lv's study, the volume of infusion within 24 hours is lower than that of patients in low altitude areas, which in order to prevent the occurrence of pulmonary edema, brain edema and heart failure [19]. This is consistent with Liu's ndings [7,43], which believe that small volume of 7.5% hypertonic saline/6% dextran could better resuscitate hemorrhagic shock with pulmonary edema at high altitude. It is worth noting that in the process of rehydration, which necessary to monitor the patients' physiological indicators (blood pressure, pulse, urine volume and central venous pressure), and adjust the rehydration speed according to the monitoring situation [13].…”
Section: Discussionmentioning
confidence: 62%
“…According to Hongmin Lv's study, the volume of infusion within 24 hours is lower than that of patients in low altitude areas, which in order to prevent the occurrence of pulmonary edema, brain edema and heart failure [19]. This is consistent with Liu's ndings [7,43], which believe that small volume of 7.5% hypertonic saline/6% dextran could better resuscitate hemorrhagic shock with pulmonary edema at high altitude. It is worth noting that in the process of rehydration, which necessary to monitor the patients' physiological indicators (blood pressure, pulse, urine volume and central venous pressure), and adjust the rehydration speed according to the monitoring situation [13].…”
Section: Discussionmentioning
confidence: 62%
“… 4 This lethal syndrome can be caused by multiple factors that span multiple systems such as severe burns, deep cuts, gunshot wounds, trauma, and amputations. 5 For patients with traumatic hemorrhagic shock induced by severe multiple injuries, ensuring heart rate, maintaining smooth breathing, controlling bleeding, and shock recovery should be proceeded priority. Based on such principle, Limited Fluid Resuscitation (LFR), permissive hypotension, blood component transfusion, and control of traumatic coagulopathy are the basic treatments for traumatic hemorrhagic shock.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%